Extreme Narration in Rexina Vega’s Ninguén Dorme (2019). Pariah’s Body, Empowerment and Feminine Violence - Garrido González, Ana (Madrygal. Revista de Estudios Gallegos, 2020)
In this work we will approach Rexina Vega’s Ninguén Dorme (2019) to analyse how the author had to rebuild, from marginalization, a new authorial figure which could boost the visibility of a book that conceives its message’s violence as a tool that forces the reader to deal with what society evade -misery, racism, gender-based violence, paedophilia, etc. We will prove that the political and literary artefact built by the author is a completely new method to address the social novel in a way that transforms the corporal and emotional conflict from a repulsive reality into a space from where to think again. It is a radical proposal focussing its discourse in women’s bodies, enjoyment and fears, narrating fundamental experiences as abortion and women’s defensive violence. In order to spell out Vega’s text, we will base our analysis on Georges Bataille’s theories about erotism and violence, but also on Hannah Arendt in order to address the pariah figure, on Luce Irigaray to enquire into the reasons behind feminine definition founded on masculine desire, on Donna Haraway to analyse the woman with a vagina dentata as a monster and on Julia Kristeva and her theories about the concept of abject.
Keywords: Body; Sex; Violence; Pariah; Marginal Authorial Construction